Anticausatives with passives of subordinate intransitive clauses in Xitsonga - Hlungwani, Madala Crous (Stellenbosch Papers in Linguistics Plus, 2019)
Literature shows that anticausatives have been well investigated in European languages such as English, German, and Greek. However, this is not the case with African languages, particularly Bantu languages such as Xitsonga. The available evidence suggests that there remain unanswered questions about anticausatives across languages. This article, therefore, is an attempt to reduce this knowledge gap by providing a perspective that seems to have been overlooked in previous studies, namely how anticausatives and passives can interact and complement each other in a single construction. In Xitsonga, anticausatives are marked by the presence of neuter-passive morpheme -ek- on the verb, for example, -hlanhl-a ‘smash to pieces’ > -hlanhl-ek-ile ‘smashed to pieces’, while the passives are marked by the morpheme -iw-, for example, -hlanhl-iw-ile ‘smashed to pieces’. The anticausatives in this paper occur as the main clause while the passives occur as the subordinate hikuva ‘because’ reason clause. The main concern of the present paper is to determine the modification of the passive of the subordinate clause by the PPs denoting agents, instruments, and causers/causing events. On the whole, this paper finds that Xitsonga passives of the subordinate intransitive clause may be modified by PPs denoting agents, instruments (pure-instruments), and causers (instrument-causers) when the verb in such a clause is a motion verb with a reduplicated stem, or a weather verb, and when the passive morpheme co-occurs with the causative morpheme.